Efek Perbedaan Temperatur terhadap Aktivitas Tripsin-Like dan Amilase Digesti Ikan Lunjar (Rasbora lateristriata Blkr.) - Fadhna Alunka Majid; Untung Susilo; Eko Setio Wibowo; Yulia Sistina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Previous studies related to digestive enzyme activity have been carried out, but there is no information related to the effect of temperature on the trypsin-like activity and digestive amylase in Rsbora lateristriata. Therefore, the purpose of this study was to determine the effect of temperature differences on the activity of trypsin-like and amylase digestion of Rasbora lateristriata fish. The temperature treatments applied were 20, 30, 40, 50, 60, and 70ºC and each treatment was repeated five times. A total of 125 Rasbora fish with a body weight of 0.81 ± 0.09 grams were used in this study. Trypsin-like and amylase activities were measured using a spectrophotometer. The results showed that there were significant differences (p < 0.05) in the trypsin-like and amylase activities at different temperatures. The trypsin-like activity was not significantly different (p < 0.05) between 20-50ºC, but the activity was lower at 60-70ºC. Amylase activity at 30°C and 40°C was not significantly different (p < 0.05), but significantly different from 20, 50, 60, and 70°C. In conclusion, trypsin-like decreased activity at 60°C and amylase at 50°C.